Análisis de la serie de televisión “Black Mirror” desde las categorías de distopía social, futuro de los medios de comunicación y evolución tecnológica - Alarcón Ortega, Angel Humberto (2026)
This research analyzes how the television series Black Mirror, created by Charlie Brooker, represents a technological evolution and its impact on the configuration of social dystopias and on the transformation of media. Through the study of 27 episodes and the interactive film Bandersnatch, explain the narrative, aesthetic and social implications that these representations build on the contemporary use of technology and media. The methodology applied was qualitative and based on the analysis of audiovisual, visual and narrative content, complemented by interviews with experts in the audiovisual, sociological and communicational fields. The results show that social dystopia constitutes a transversal axis in most of the episodes analyzed. Black Mirror portrays scenarios where technologies amplify problems. Likewise, the series is presented through innovations such as artificial intelligence, the digitalization of consciousness. Making technology work as a catalyst for human conflict and thus evidencing a critique of power structures and the lack of ethics in the appropriation of technology. The series uses very precise narrative and visual resources to support the speech it handles, this evidenced in cold atmospheres, intimate frames, strategic silences, reinforcing the dystopian. Similarly, expert interviews confirmed the critical value of the series, highlighting its ability to generate reflective thinking in the audience and its usefulness as a tool for academic analysis. It concludes that the series is a key reference for understanding the contemporary tensions between technology, media and society and how they coexist in a new hyper-connected society